Study of oxaliplatin penetration into ovaries of patients treated with hyperthermic intraperitoneal chemotherapy (HIPEC) for peritoneal metastases of colorectal and appendiceal origin using mass spectrometry imaging - Larroque, Marion (Pleura Peritoneum, 2021)
OBJECTIVES: Platinum salts are commonly used in hyperthermic intraperitoneal chemotherapy (HIPEC) for digestive tract cancer treatment. During HIPEC with oxaliplatin for peritoneal metastases (PMs) treatment, the ovaries are directly exposed to the drug, questioning about ovarian resection and the potential impact of the drug on ovarian functionality, especially in young women of childbearing age. The goal of this work is to understand unwanted damages to the ovaries during HIPEC therapy by the determination of the concentration and distribution of platinum in ovaries in order to address its potential toxicity. METHODS: Mass spectrometry imaging techniques, matrix-assisted laser desorption ionization mass spectrometry (MALDI-MS) and laser ablation inductively coupled plasma mass spectrometry (LA-ICP MS), were used to study the penetration of oxaliplatin in ovaries after HIPEC treatment. RESULTS: MALDI-MS allowed the localization of an oxaliplatin-derivative (m/z 456.2) at the periphery of the ovaries. The quantitative LA-ICP MS maps confirmed the localization of elemental platinum as well as in the central part of ovaries from patients who received a previous platinum salt-based chemotherapy. CONCLUSIONS: LA-ICP MS images showed that platinum diffusion was extended in cases of previous systemic treatment, questioning about platinum derivatives gonado-toxicity when combining the two treatments.